Politeness Strategies Used by the Main Characters in The Garfield Movie: A Pragmatic Perspective - Mubarok, Tyas Alhim (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This study investigates the politeness strategies employed by the main characters in The Garfield Movie from a pragmatic perspective, using Brown and Levinson’s (1987) politeness theory as the analytical framework. By analyzing selected dialogues, the research identifies four main types of politeness strategies: bald on record, positive politeness, negative politeness, and off-record strategies. The findings reveal that positive politeness strategies are predominantly used to maintain social harmony and express friendliness, while bald on record strategies reflect the characters’ directness and humor. Negative politeness strategies appear less frequently, mainly to mitigate impositions and show respect, and off-record strategies serve to convey subtlety and indirectness, often adding comedic effect. The study highlights how these strategies align with the characters’ personalities and relationships, contributing to effective communication and audience engagement. The implications of this research extend to pragmatic theory, language teaching, media scriptwriting, and intercultural communication, emphasizing the value of media texts as authentic sources for pragmatic learning and analysis.